2017
DOI: 10.1101/158642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type 2 Diabetes Risk Alleles Reveal a Role for Peptidylglycine Alpha-amidating Monooxygenase in Beta Cell Function

Abstract: 149Word count: 4500Number of tables and figures: 5 . CC-BY-NC-ND 4.0 International license peer-reviewed) is the author/funder. It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/158642 doi: bioRxiv preprint first posted online Jul. 3, 2017; 2 ABSTRACT Molecular mechanisms underpinning the genetic risk for type 2 diabetes (T2D) remain poorly understood, hindering translation into new therapies. Recently, genome-wide studies identified two coding va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The D563G variant was identified in another European large‐scale whole‐genome sequencing study, and was shown again to be associated with increased T2D risk . PAM polymorphisms may directly contribute to islet secretory defects, as a recent report showed that human islets from D563G variants have a modest impairment in insulin granule exocytosis …”
Section: Peptidylglycine α‐Amidating Monooxygenasementioning
confidence: 99%
See 2 more Smart Citations
“…The D563G variant was identified in another European large‐scale whole‐genome sequencing study, and was shown again to be associated with increased T2D risk . PAM polymorphisms may directly contribute to islet secretory defects, as a recent report showed that human islets from D563G variants have a modest impairment in insulin granule exocytosis …”
Section: Peptidylglycine α‐Amidating Monooxygenasementioning
confidence: 99%
“…For example, ChgA is processed into the vasostatins, pancreastatin, catestatin, parastatin and other products . Although little is known regarding the relative abundance of ChgA‐ and ChgB‐derived peptides in β‐cells, and their local effect on islet function, loss of Pam‐mediated amidation of ChgA has recently been suggested as a contributor to β‐cell dysfunction in carriers of Pam variants . ProSAAS, an inhibitor of Pc1/3, and 7B2 (secretogranin V), an inhibitor and chaperone of proPc2, are also synthesized as propeptides in β‐cells, and processed to mature products.…”
Section: Islet Endocrine Cell Prohormone Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene-level signal in PAM also remained nominally significant ( p <0.05) even after removing the 35 strongest individually associated PAM variants, indicating a contribution from substantially more variants than p.Asp563Gly and p.Ser539Trp ( Supplementary Figure 14 ). Cellular characterization of p.Asp563Gly and p.Ser539Trp recently identified a novel mechanism for T2D risk through altered insulin storage and secretion 46 . Our results provide many more genetic variants – identifiable only through sequencing 17 – that could be characterized for further insights into the T2D risk mechanism mediated by PAM .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there should be different pathophysiological pathways for the development of the condition. Many of these mechanisms have been shown to have a genetic predisposition, including; Proopiomelanocortin gene mutation, Melanocortin receptor mutations, brain-derived neurotrophic factor and receptor mutations, glucose kinase mutations, hepatocyte nuclear factor mutations, mitochondrial DNA mutations, Insulin receptor mutations, viral oncogene homolog 2 (AKT2), v-akt murine thymoma and even lipodystrophy can alter the normal function of β-cell [29][30][31][32][33]. Apoptosis appears to be the leading cause of β-cell destruction in both types of diabetes mellitus through activation of interleukin (IL)-1β, nuclear factor (NF)-κB, and Fas pathways, through a process, known as insulitis [34].…”
Section: Pathogenesis Of β-Cells Dysfunctionmentioning
confidence: 99%